Network size variation of geographical aided routing protocols in MANET - Radhwan B. Al-Bayram; Radhwan M. Abdullah (Institute of Advanced Engineering and Science, 2021)
In position-based or geo-casting ad hoc networking applications, the data packets flooded in a limited area of the expected region toward the destination node. In such networks, a multi-hop routing is to followed when the position of the destination node is residing off-range the wireless transmission of the source node. Scientific literature references in this concept have been conducted depended on the diversity of quantitative metrics-tests regarding the size of the assigned networks so that this space is intended to be the variation in the density of the moving nodes (the number of nodes per unit of measurement). In this work, we studied the impact of the change in the size (area) of the ad hoc network with the concept of variation in the network's area while remaining the total number of nodes as a constant volume. In this paper, three of the position-based routing protocols have evaluated in terms of a network size variation. These routing protocols are: locations aided routing LAR, the distance routing effect algorithm for mobility DREAM, and the greedy perimeter stateless routing GPSR. With each simulation test, a quantitative metrics evaluation determined the most efficient protocol and the most efficient accessibility with the network environment changes in terms of actual workspace.